Easy knowledge engineering and usability evaluation of longan knowledge-based system - Churee Techawut (2018)
Longan has been regarded as an important economic fruit for export of Thailand. In order to support Thai longan growers, the Thai government has set a strategic plan to enhance longan production and knowledge distribution by funding research and development, and constructing of Longan Knowledge-based System (LKS). This paper presents the construction process of LKS called 'easy' knowledge engineering, involving ontology modeling for construction of longan knowledge structure and preparation of data instances. LKS provides (1) unsophisticated tools with usability for searching some related knowledge con-cepts, and (2) 'easy' knowledge that was compiled, according to the designed ontology, into different basic core data representation. In addition, this paper demonstrates a usability study in evaluation of LKS based on ISO 9241 usability standard. The results show that LKS has a usability, and users highly satisfy with searching interaction and retrieving 'easy' knowledge.